2010
DOI: 10.1002/jor.21061
|View full text |Cite
|
Sign up to set email alerts
|

Action of IL‐1β during fracture healing

Abstract: After bone injury, developmental processes such as endochondral and intramembranous ossification are recapitulated as the skeleton regenerates. In contrast to development, skeletal healing involves inflammation. During the early stages of healing a variety of inflammatory cells infiltrate the injured site, debride the wound, and stimulate the repair process. Little is known about the inflammatory process during bone repair. In this work, we examined the effect of a pro-inflammatory cytokine, Interleukin-1 beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
112
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(124 citation statements)
references
References 32 publications
10
112
0
2
Order By: Relevance
“…Platelets play a pivotal role in these early phases of healing. IL-1 19 and IL-6 20 as pro-inflammatory cytokines play a role in macrophage activation. IL-17 was shown to be one of the key regulators in the early phases of bone healing via osteoblast maturation.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets play a pivotal role in these early phases of healing. IL-1 19 and IL-6 20 as pro-inflammatory cytokines play a role in macrophage activation. IL-17 was shown to be one of the key regulators in the early phases of bone healing via osteoblast maturation.…”
mentioning
confidence: 99%
“…In biomaterials research, TNF-α and IL-1 are the best known mediators of the foreign body reaction. Lange et al 19 observed the positive effect of IL-1β on the proliferation of osteoblasts and the negative effect on the proliferation and differentiation of MSCs. Similarly, TNF-α was shown to inhibit the progress of bone healing by inducing osteoblast and chondrocyte apoptosis.…”
mentioning
confidence: 99%
“…Unlike TNF-a, which does not affect skeletal development but is required for normal bone regeneration, absence of IL-1 does not affect in vivo fracture healing. 91 However, mice lacking IL-1a and/or IL-1b, the two forms of IL-1, have significantly higher bone mineral density and femoral bone mass than normal mice, which has been attributed to impaired osteoclast development. 92 In vitro studies of the effects of IL-1a and IL-1b on osteogenically differentiating MSCs have shown that these cytokines have similar effects as TNF-a.…”
mentioning
confidence: 99%
“…In the current study, the influences of cell-cell interaction arising from the difference in transplanted cell numbers between the two groups was not considered, which should be regarded as a limitation. It is well known that inflammatory signals play an important role in regulating fracture healing (42,49). In the early stages of fracture healing, the mRNA expression levels of inflammatory cytokines, including TNF-a, IL-1, and IL-6, are significantly elevated within the first few days after injuries at the perifracture sites (9,19,37,52).…”
Section: Discussionmentioning
confidence: 99%